Stratifikasi Massa Air di Teluk Lasolo, Sulawesi Tenggara - Edi Kusmanto; Dewi Surinati, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Stratification of Water Mass in Lasolo Bay, Southeast Sulawesi. As a nature conservation area, Lasolo Bay should be supported by data and information of waters oceanographic. Research for stratification of water masses in Lasolo Bay was conducted. from 10 to 19 July 2011. Temperature and salinity data were obtained using CTD SBE 911 Plus preinstalled on Research Vessel Baruna Jaya VIII at intervals of 24 data per second. Current data were obtained using Vessel Mounted Acoustic Doppler Current Profiler (VMADCP) with an interval of two seconds. The results show that there are differences in the speed and direction of currents in the water column that lead to stratification of water masses. Currents that drove the water mass of Banda Sea into Lasolo Bay was caused by southeasterly winds with an average speed of 4.1 m/s. At depths of 0–50 m and 100–200 m the current dominance occurs to the northwest, while at depths of 50–100 m and 200–350 m it occurs to the south. The water mass with a salinity of 32.1–34.0 PSU and temperature 26–28°C occupied the surface layer (0–50 m). The water mass with a salinity of 34.4–34.5 PSU identified as the water mass of North Pacific Intermediate Water (NPIW) occupied two depths, i.e. 50–100 m and 200–350 m with different range of temperatures. The water mass with maximum salinity (34.5–34.6 PSU), identified as the water mass of North Pacific Subtropical Water (NPSW) also occupied two depths i.e. 100–200 m and 350 m until near the bottom with different range of temperatures